2012
DOI: 10.1371/journal.pone.0038576
|View full text |Cite
|
Sign up to set email alerts
|

CC8 MRSA Strains Harboring SCCmec Type IVc are Predominant in Colombian Hospitals

Abstract: Background Recent reports highlight the incursion of community-associated MRSA within healthcare settings. However, knowledge of this phenomenon remains limited in Latin America. The aim of this study was to evaluate the molecular epidemiology of MRSA in three tertiary-care hospitals in Medellín, Colombia. Methods An observational cross-sectional study was conducted from 2008–2010. MRSA infections were classified as either community-associated (CA-MRSA) or healthcare-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 44 publications
8
56
1
6
Order By: Relevance
“…Both were present in all three types of infection. This result supports the previous reports of studies in our country, which have shown the predominance of the SCCmec IVc subtype among isolates, followed by a smaller proportion for SCCmec IVa (40,41).…”
Section: Clinical Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Both were present in all three types of infection. This result supports the previous reports of studies in our country, which have shown the predominance of the SCCmec IVc subtype among isolates, followed by a smaller proportion for SCCmec IVa (40,41).…”
Section: Clinical Analysissupporting
confidence: 93%
“…Among the MRSA isolates tested in our study, 88% carried the lukS/F-PV genes, and these genes were detected in all SCCmec types identified (SCCmec IVc, Iva and I). In Colombia, there have been several reports of infections caused by PVL-positive MRSA strains carrying SCCmec IVc belonging to clonal complex 8 (CC8) in hospitals (13,(41)(42)(43). In a recent previous work, we reported the ST8-MRSA-IVc clone as the main strain causing HAI (13).…”
Section: Clinical Analysismentioning
confidence: 94%
“…Se incluyeron aislamientos de SARM obtenidos de pacientes hospitalizados con infección, y recolectados en dos periodos diferentes: 67 aislamientos recolectados de forma prospectiva, obtenidos durante el año 1994, y 331 aislamientos recolectados de forma prospectiva y obtenidos entre febrero de 2008 y junio de 2010. Estos últimos aislamientos hacían parte de un estudio reportado previamente (14). En ambos periodos de estudio se incluyó una muestra por paciente correspondiente al primer aislamiento clínico de SARM obtenido durante el proceso infeccioso.…”
Section: Población De Estudiounclassified
“…En Colombia se han identificado clones de SARM-AH como el pediátrico, el brasilero y el chileno/cordobés, principalmente en hospitales de tercer nivel en Bogotá (9)(10)(11). Asimismo, el clon de SARM-AC USA300 (CC8-ST8-SCCmecIV) se ha descrito como causante de infecciones hospitalarias (12)(13)(14).…”
unclassified
“…En Colombia y en varios países de Suramérica se ha reportado la diseminación de aislamientos SARM asociados a la comunidad (SARM-AC), los cuales causan infecciones no solo en personas en la comunidad, sino también en pacientes hospitalizados (8)(9)(10)(11). La mayoría de estos aislamientos presentan características moleculares similares al clon USA300 diseminado en Estados Unidos: la ST8 y los genes lukS-PV/lukF-PV, seq, sek y bsa (8)(9)(10).…”
unclassified